2019
DOI: 10.1080/16583655.2019.1651520
|View full text |Cite
|
Sign up to set email alerts
|

Goal programming approach to fully fuzzy fractional transportation problem

Abstract: In this paper, authors devoted to study a fully fuzzy fractional multi-objective transportation problem by using goal programming approach. Also trapezoidal membership functions are applied to each objective function and constraints to describe a each fuzzy goal. A numerical example is provided to illustrate the efficiency of the multi-objective proposed approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Similar studies that use max-min operators within the extension principle applied to linear and linear fractional transportation problems can be found in the literature, see, for instance, [8][9][10][11][12][13][14][15][16]. Another related area is Data Enveloped Analysis (DEA) in fuzzy environments.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Similar studies that use max-min operators within the extension principle applied to linear and linear fractional transportation problems can be found in the literature, see, for instance, [8][9][10][11][12][13][14][15][16]. Another related area is Data Enveloped Analysis (DEA) in fuzzy environments.…”
Section: Introductionmentioning
confidence: 87%
“…In what follows, we extend the LP problem to an FF-LP problem, referring only to its standard maximization form, without loosing any generality. Model (9) provides the full fuzzy extension to Model (8).…”
Section: Problem Formulation and Solution Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the fractional calculus has gained the importance and popularity for the modelling of the real-world problems [22][23][24][25][26][27][28]. However, many scientists have shown that the conventional form of the fractional derivatives with singular kernel may not be able to characterize the nonlocal dynamics in an appropriate manner; hence, to better investigate the real-world phenomena with hereditary property, there is a need to apply new types of the fractional operators with nonsingular kernel.…”
Section: Introductionmentioning
confidence: 99%